Development of Mount Sinabung Refugee Relocation Areas Through Tourism Villages in the Siosar Area, Karo District, North Sumatra Province - Linnga, Osland Herijon; Sirojulizam, Sirojulizam; Purwoko, Agus; Thoha, Achmad Siddik (Journal of Ecohumanism, 2024)
Regional development planning is aimed at achieving harmony and balance in development between regions in accordance with their natural potential and utilizing this potential in an efficient, orderly and safe manner. For this reason, based on Law no. 24 of 1992 concerning Spatial Planning, a National Spatial Plan (RTRWN) has been drawn up which has been stipulated through Government Regulation no. 47 of 1997 as a reference for national development planning. The development of the relocation area for Siosar Village, Karo Regency, requires support from relevant stakeholders, namely the Karo Regency Government, the Karo DPRD and Entrepreneurs. It is hoped that this will further strengthen the development of the Siosar Village relocation area into a Tourism Village. The urgency of this research is to find out the potential for opening the Siosar tourism village to become a tourist village and from a socio-economic point of view of the community. The data collection technique is to distribute questionnaires to stakeholders including the public and visitors. The data analysis technique used uses the smartPLS approach and the result is that there are socio-economic influences on the community in regional development. The socio-economic community also has an influence on tourist villages. The tourism village has an influence on regional development and through the Sobel test, the tourism village variable is able to mediate the socio-economic conditions of the community towards regional development.